A Teologia Latino-Americana desafiada a reprojetar-se : Interpelações do novo contexto (Razão e Fé, 2023)
Based on seven main aspects that characterize Latin-american theology, it seeks to identify the new questions arising from the new context in which we live, especially for its epistemology and method. These are challenges that lead to a necessary re-projection of a way of doing theology, a condition for continuing to feed back into the praxis of ecclesial communities prophetically inserted in a society undergoing profound transformations. In the context of the crisis of the modern civilizational project, it is not only Latin-american theology that is in crisis, but theology itself, participants in a crisis of technical-instrumental reason, characteristic of modern reason, challenged to broaden its horizons, to be able to embrace the new realities and emerging values.